Analisis Kelayakan Usaha Gula Aren di Kelompok Tani Tanisari Desa Ngargosari Kecamatan Loano Kabupaten Purworejo - Fatmawati, Nurlaila; Alim, M Abdul Rohman; Barokah, Umi; Nugroho, Rahmat Joko; Muflih, Ghufron Zaida (Jurnal Agroteknologi (Agronu), 2025)
Ngargosari Village is one of the palm sugar producing villages in Loano District. The palm trees in Ngargosari Village are not cultivated; they grow naturally and are cultivated through generations, with the number of palm trees reaching 3,000. This study aims to determine the business analysis of costs, revenue, income, as well as the feasibility analysis of R/C and BEP (BEP unit and price) of palm sugar production per month in the "Tanisari" Farmer Group, Ngargosari Village, Loano District, Purworejo Regency. The sampling method used is a census, namely all individuals in the population are counted (investigated or interviewed) as respondents with a total of 25 palm sugar craftsmen. The data collected are primary data and secondary data. The analysis method used is a business feasibility analysis using the R/C Ratio and BEP. The results of this study show: (1) The average production costs incurred by palm sugar craftsmen are Rp. 748,600, (2) The average income earned by palm sugar craftsmen is Rp. 1,518,600, and (3) the income earned by palm sugar craftsmen is Rp. 770,000 in one month of production. (4) The amount of R/C in the palm sugar agroindustry shows that the craftsmen are profitable and worth pursuing because it has been proven to provide benefits to the craftsmen. The R/C in the palm sugar agroindustry is 2.03, indicating that for every Rp. 1 of costs incurred in the agroindustry, revenue of Rp. 2.03 will be obtained, so the income obtained is Rp. 1.03. (5) The BEP unit size is 38 kg < the production unit in the research area is 75 kg, the BEP price result is IDR 9,981 < the price in the research area is IDR 19,400, so it can be concluded that the palm sugar business is financially feasible to develop